Nursing care of crack to user: reflections from the perspective of the principles of holistic theory - Fernando José Guedes da Silva Junior Fernando Guedes; Larissa Alves de Araújo Lima Larissa Alves; Iara Jéssica Barreto Silva Iara; Grazielle Roberta Freitas da Silva Grazi; Maria Helena Barros Araújo Luz Maria; Claudete Ferreira de Souza Monteiro claudete (Universidad de Alicante, 2014)
The consumption of crack incites a default intense, continuous and repetitive, causes and consequences violate the user extends to all his family and social environment. Given this reality aimed to reflect on the nursing care of crack users and their interface with the Holistic Theory proposed by Myra Levine. The Holistic Theory is emphasized as connection and link between the fragment and the whole, through the knowledge of human parts: body-mind-spirit-nursing-client-family. This conceptual framework has logical nature, is simple, generalizable and can be tested based on assumptions. Thus, nurses must understand the crack user as a bio-psychosocial being the repercussions of the use of this substance transgress the physical dimension, greatly complicating the traditional nursing care. In this context, it is imperative to support holistic and humane able to foster face this serious problem.